Reply - Messer, Mirko; Ringleb, Peter A.; Nagel, Simon (American journal of neuroradiology, 2017)
We appreciate the comments by Gallerini et al regarding our recently published Clinical Report on patients with minor acute ischemic stroke syndromes and underlying large-vessel occlusion (LVO) in the anterior circulation. We agree that in most stroke centers today, there is equipoise as to whether